Pendampingan Digitalisasi Ingatan Tentang Sejarah, Kesenian Dan Tradisi Warga Sungai Bahar - Pradita, Dennys; Mustafa, Hanif Risa; Pratama, Amor Gilang Seta; Lestari, Inda; Mahanani, Nugrahadi (Yayasan Sagita Akademia Maju, 2024)
Community memory is a legacy that has a very high value for a community or region. Community memories can be dangerous because they fade and even disappear. This paper will describe a program to document the memories of transmigrant communities in Sungai Bahar. This service program uses data collection modalities by collecting memories through interviews and then documenting them. The community that inhabits the Sungai Bahar area has been around since the 1980s. With the development of time, these speakers are getting older and decreasing in number. The existence of this documentation is a step to document memories so that future generations can know the origin and development of the region which can be accessed through gadgets so that the history and culture of the region does not fade with time.